2019
DOI: 10.3892/or.2019.7286
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy modulation in bladder cancer development and treatment (Review)

Abstract: Bladder cancer (BC) is a potentially life-threatening malignancy. Due to a high recurrence rate, frequent surveillance strategies and intravesical drug therapies, BC is considered one of the most expensive tumors to treat. As a fundamental evolutionary catabolic process, autophagy plays an important role in the maintenance of cellular environmental homeostasis by degrading and recycling damaged cytoplasmic components, including macromolecules and organelles. Scientific studies in the last two decades have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…Previous studies found that BC exhibit a high basal level of autophagic activity that may reduce the effectiveness of current anticancer treatment, a process known as protective autophagy 23 . Therefore, we sought to identify the role of miconazole in protective autophagy, the transmission electron microscopy (TEM) was utilized for analyzing morphological features of autophagy in BC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that BC exhibit a high basal level of autophagic activity that may reduce the effectiveness of current anticancer treatment, a process known as protective autophagy 23 . Therefore, we sought to identify the role of miconazole in protective autophagy, the transmission electron microscopy (TEM) was utilized for analyzing morphological features of autophagy in BC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that BC exhibit a high basal level of autophagic activity that may reduce the effectiveness of current anticancer treatment, a process known as protective autophagy. 23 an mTOR-independent manner. 25 We revealed that miconazole promoted AMPK phosphorylation ( Figure 2D,E) and inhibited the activity of AKT ( Figure S1C), suggesting that miconazole promotes autophagy function via AMPK upregulation and AKT downregulation.…”
Section: Miconazole Promotes Lc3 and P62 Expression In Human Bc Cellsmentioning
confidence: 98%
“…The ULK kinase complex phosphorylates and activates autophagy and beclin-1 regulator (AMBRA) protein, and AMBRA then phosphorylates a class III phosphoinositide 3-kinase (PI3K) complex consisting of Beclin1, ATG14L, VPS34 and VPS15 [ 16 ]. The activated PI3K complex can now convert phosphatidylinositol-4,5-bisphosphate (PIP2) to phosphatidylinositol-3,4,5-bisphosphate (PIP3) [ 47 ]. The elevation of the surrounding PIP3 concentration attracts another two proteins called WD repeat domain phosphoinositide-interacting protein (WIPI2) and zinc-finger FYVE domain-containing protein 1 (DFCP1) to the PAS membrane [ 46 ].…”
Section: Autophagy Types and Process And Functional Roles Of Autophamentioning
confidence: 99%
“…In contrast, O. tsutsugamushi the etiologic agent of scrub typhus, a disease endemic to the Asian continent and present throughout Indonesia and northern Australia, is transmitted mainly by the bite of larva life stage-infected Leptotrombidium mites (49,50). HME, HGA and scrub typhus have similar clinical presentations characterized by initial symptoms including fever, headache, myalgia, nausea, confusion, conjunctival injection (red eyes), and chills within the first two weeks following infection (1,3,15). Common laboratory abnormalities include thrombocytopenia, leukopenia, anemia, and elevated hepatic transaminases (2,14,(16)(17)(18).…”
Section: Anaplasmataceae: Intracellular Pathogens Of Life-threatening Human Infectionsmentioning
confidence: 99%
“…The autophagic process can be divided into distinct stages, including autophagy induction, phagophore formation and elongation, cargo recognition, autophagosome maturation, lysosomal fusion and autophagosome degradation (13,15). In coordination with these steps are several major signaling pathways and autophagy-related genes (ATGs).…”
Section: Introductionmentioning
confidence: 99%